Climate change and small-scale farmer livelihood adaptation in rural border communities in Southern Africa: A case study of Ezondweni Village in Mchinji, Malawi - Simango, Kennedy Khuzwayo (Rhodes University, Faculty of Humanities, Department of Social Science)
Southern Africa is a region increasingly experiencing the detrimental effects of climate change and variability. The rural areas in particular face unprecedented climate change-induced challenges in relation to small-scale farmers being able to pursue household-based livelihoods, and these farmers seek ways of adapting to climate change and variability in doing so. Some rural communities exist along territorial borders and their attempts at adapting to climate change entails cross-border networks and activities. In this context, this thesis examines small-scale farmer adaptation to climate change and variability in the small village of Ezondweni in Malawi near the Zambian border. Analytically, the study draws upon the Sustainable Livelihoods Framework as well as social network theory and the theory of reflexive agency put forward by Margaret Archer. A qualitative research design entailed informal interviews with a small number of Ezondweni villagers, focusing on their perceptions of climate change and their practices of climate change adaptation. The study demonstrates the diverse activities pursued by villagers, both within Malawi and beyond, in seeking to maintain household-based livelihoods, as well as the significance of mutually-supportive social networks which facilitate these livelihood processes.
Keywords: Farms, Small -- Malawi -- Mchinji; Climatic changes -- Economic aspects -- Malawi -- Mchinji; Climatic changes -- Risk management -- Malawi -- Mchinji; Crops and climate -- Malawi -- Mchinji; Sustainable agriculture -- Malawi -- Mchinji; Farmers -- Social networks -- Malawi -- Mchinji; Farm income -- Malawi -- Mchinji